1994
DOI: 10.1523/jneurosci.14-05-03370.1994
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of agonist and antagonist activities of phenylglycine derivatives for different cloned metabotropic glutamate receptor subtypes

Abstract: The metabotropic glutamate receptors (mGluRs) consist of at least seven different subtypes and are coupled to intracellular signal transduction via G proteins. However, the lack of specific antagonists for the mGluRs limited the precise characterization of the role of the individual mGluRs. In this study, we investigated the agonist and antagonist activities of a series of phenylglycine derivatives for the mGluRs by examining their effects on the signal transduction of representative mGluR1, mGluR2, and mGluR4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
189
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(206 citation statements)
references
References 26 publications
16
189
0
1
Order By: Relevance
“…Its derivative, S-MCPG, is a nonselective antagonist for group I and II receptors (5-7), whereas it has little or no activity with group III receptors (6,22). All of the residues that directly recognize the antagonist are completely conserved among all of the groups, except for Y74.…”
Section: H]quisqualate Binding To M1-lbr Is Displaced By S-mcpgmentioning
confidence: 99%
See 1 more Smart Citation
“…Its derivative, S-MCPG, is a nonselective antagonist for group I and II receptors (5-7), whereas it has little or no activity with group III receptors (6,22). All of the residues that directly recognize the antagonist are completely conserved among all of the groups, except for Y74.…”
Section: H]quisqualate Binding To M1-lbr Is Displaced By S-mcpgmentioning
confidence: 99%
“…To obtain clearer insights into the structural basis of receptor activation, we have determined the crystal structure of m1-LBR complexed with an antagonist, (S)-(␣)-methyl-4-carboxyphenylglycine (S-MCPG) (5)(6)(7). Furthermore, we have solved the crystal structure in the presence of both the native agonist, L-glutamate, and gadolinium ions, because metal cations, including Gd 3ϩ , modulate the signaling of mGluRs (8)(9)(10)(11).…”
mentioning
confidence: 99%
“…That MSOP inhibited ACPD-induced death to a similar level as MCPG suggested that the group III mGluRs were responsible for ACPD-induced death. However, MCPG has previously been shown to be ineffective at antagonising responses mediated by the group III subtypes mGluR4 and mGluR7 (Hayashi et a!., 1994;Saugstad et al, 1994;Thomsen et a!., 1994). In addition, ACPD has generally been assumed to be relatively ineffective as an agonist at group III mGluRs, and cloned group ifi mGluRs are distinguished by their insensitivity to ACPD, and their sensitivity to L-AP4 (see Pin and Duvoisin, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…5A and D). More importantly, 4C3HPG, which is a competitive antagonist of mGluR1a (Kingston et al, 1995) but an agonist of group II receptors (Hayashi et al, 1994), stimulated [Ca 2+ ] i increases in cells expressing both mGluR3/1a and mGluR2/1a chimeric receptors ( Fig. 5A and D).…”
Section: Ctz Does Not Bind To the N-terminus Of Mglur1amentioning
confidence: 92%